Application Of Three-Dimensional (3D) Visual Learning Media In Cooperative Learning Model In Improving Student Learning Outcomes Of Class XI High School Students On Chemical Bonding Material - Hasian P.K.A Silalahi; Febri Yanti; Hendra Simanjuntak (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
This research aims to see Application of Three-Dimensional (3D) Visual Learning Media in the Cooperative Learning Model in Improving Learning Outcomes of Class Xi High School Students on Chemical Bonding Material. The research location will be carried out at SMA Negeri 6 Pematangsiantar and the implementation time will be in the odd semester of the 2024/2025 academic year starting from August to September 2024. The sample is a subtest or part of the population selected to participate in the research. This sample is taken from a larger population and must be representative of that population so that the research results can be generalized. Research instruments are tools or devices used by researchers to collect data relevant to the research objectives. This instrument can take the form of a test, interview, observation, or other technological device that suits the type of data needed. The conclusion of this research is that the selection and application of three-dimensional visual learning media in the learning process can improve students' learning outcomes. This can be proven in this research by the increase in student learning outcomes in the experimental class as seen through the tcount value obtained, namely 18.094, this value is greater than the value in the ttable, namely 1.699 and for the sigi (2 tailed) value obtained, namely 0.000, smaller than The α value (0.05) means that in this case it can be concluded that there is an influence of three-dimensional visual learning media in improving the learning outcomes of class XI students on chemical bonding material. Keywords: Application, Three Dimensional (3d) Visual Learning Media, Cooperative Learning, Learning Outcomes